Gender based violence prevention education program in primary schools - Zúñiga Farfán, Giovanna (2019)
This article presents a program design for instructing elementary students and their nuclear family about gender violence with the objective of giving them the opportunity to analyze their surrounding with a critical eye and to be able to recognize the distinctive signs of subliminal and explicit gender violence. Enabling students and parents to identify, recognize and peruse these signs aims to prevent violent acts carried out within the family and consequently to generate a multiplying effect in the Peruvian society context that suffers silently the effects of gender violence in all its forms from the mellowest and socially accepted to gender based murder or hate crimes. From the education stand point the proposal is to work on a concrete action plan expecting the school and family participation in order to strength their citizenship andto protect their rights.